Using Liquid Organic Fertilizer for Banana Stems for Bean Plants of Farmers Group at Mendalo Darat Muaro Jambi Regency - Hasriati Nasution; Ubaidillah Ubaidillah; Yusfaneti Yusfaneti; Asmadi Saat (CV. Creative Tugu Pena, 2022)
The type of soil planted is Ultisol soil which has many problems with low physical and chemical properties; hence the soil fertility is low. To be able to grow peanuts optimally, it is necessary to apply fertilizer to the soil. This article was to assist groups farmer in the use of liquid banana stem fertilizer for long bean plants. The method uses Participation Action Research (PAR). Some of the mentoring programs carried out were counseling on materials and practices for making liquid fertilizer which lasted for 4 months through several stages: preliminary survey, schedule determination and outreach of extension in the manufacture of liquid organic fertilizer from banana stems for long beans. The extension is carried out in two stages, namely by the method provides material related to the manufacture of liquid organic fertilizer for banana stems and also material on how to use banana stem organic fertilizer for long bean plants. After that, it was continued by carrying out a direct demonstration in the field on how to give liquid organic fertilizer from banana stems to long bean plants in farmer groups, In addition, farmer groups can make liquid organic fertilizer from banana stems and have also been able to determine the dose for long bean plants. In the appearance of long bean growth, the leaves are very green and bear fruit after adding liquid organic fertilizer. After the implementation of this service, it can be seen that the yield of long beans has increased from 10 tons to 17.5 tons per ha. Keywords: Liquid Organic Fertilizer, Assistance Farmer Group, Banana Stems